العلاقات التاريخية العمانية الصينية دراسة تحليلية في نصوص الحوليات الصينية - الهادي, حبيب بن مرهون (ترجمة التراث العماني الرؤى والآفاق, 2022)
Keywords: Relations – Oman – Chine

Sino-Omani relations - Sudairi, Mohammed Turki al- (The Routledge handbook of China - Middle East relations, 2023)
"This handbook brings together a mix of established and emerging international scholars to provide valuable analytical insights as to how China's growing Middle East presence affects intra-regional development, trade, security, and diplomacy. As the largest extra-regional economic actor in the Middle East, China is the biggest source of foreign direct investment into the region and the largest trading partner for most Middle Eastern states. This portends a larger role in political and security affairs, as the value of Chinese assets combined with a growing expatriate population in the region demand a more proactive role in contributing to regional order. Exploring the effect of these developments, the expert contributors also consider the reverberations in great power politics, as the U.S.A., Russia, India, Japan, and the European Union also have considerable interests in the region. The book is divided into four sections: historical and policy context state and regional case studies trade and development international relations, security and diplomacy"–
Keywords: Relations – Oman – Chine

China against US Imperialism in the Arabian Sea: The Case of Oman - Matar, Linda; Kadri, Ali (Middle East Critique, 2023)
When Oman joined China’s Belt and Road Initiative to pursue economic diversification, the US intervened to stop it. Although the foundation stone for Chinese investment plans was laid in 2017, these projects were put on hold, while the US rushed to bolster its military presence in Oman. The article studies Chinese investment in Oman, accounts for what has developed so far, and highlights the reasons for which the US acted to stem the potential of non-oil development in Oman. The disruption of the China-Oman diversification project resembles the US’s targeting of China’s policy of expansion by mutual cooperation elsewhere, but with a twist: Oman sits close to two vital chokepoints, the Bab Al-Mandeb and the Hormuz straits. The article argues that such obstruction is central to the US’s mode of accumulation by militarism. Keeping Oman from auto-developing and building its autonomy makes of it a pliable client state ready to serve as an imperialist post to empire.
Keywords: Relations – Oman – Chine

Arab Merchants in Middle Period China - Chaffee, John W. (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)
Keywords: Relations – Oman – Chine